Assessment of retinal vein pulsation through video-ophthalmoscopy and simultaneous biosignals acquisition - Kolar, Radim; Vicar, Tomas; Chmelík, Jiří; Jakubicek, Roman; Odstrcilik, Jan; Valterova, Eva; Nohel, Michal; Skorkovska, Karolina; Tornow, Ralf P (Biomedical optics express, 2023)
The phenomenon of retinal vein pulsation is still not a deeply understood topic in retinal hemodynamics. In this paper, we present a novel hardware solution for recording retinal video sequences and physiological signals using synchronized acquisition, we apply the photoplethysmographic principle for the semi-automatic processing of retinal video sequences and we analyse the timing of the vein collapse within the cardiac cycle using of an electrocardiographic signal (ECG). We measured the left eyes of healthy subjects and determined the phases of vein collapse within the cardiac cycle using a principle of photoplethysmography and a semi-automatic image processing approach. We found that the time to vein collapse (Tvc) is between 60 ms and 220 ms after the R-wave of the ECG signal, which corresponds to 6% to 28% of the cardiac cycle. We found no correlation between Tvc and the duration of the cardiac cycle and only a weak correlation between Tvc and age (0.37, p = 0.20), and Tvc and systolic blood pressure (-0.33, p = 0.25). The Tvc values are comparable to those of previously published papers and can contribute to the studies that analyze vein pulsations.